Semipreparative enantioseparation of methamidophos by HPLC-UV and preliminary in vitro study of butyrylcholinesterase inhibition - Emerick, Guilherme Luz [UNESP]; Oliveira, Regina V.; Belaz, Katia Roberta A.; Goncalves, Monique [UNESP]; DeOliveira, Georgino H. [UNESP] (Wiley-Blackwell, 2012)
Many chiral pesticides are introduced into the environment as racemates, although their pesticidal activity is usually the result of preferential reactivity of only one enantiomer, while the other enantiomer may have toxic effects against nontarget organisms. Methamidophos (O,S-dimethyl phosphoramidothioate), a chiral compound, is an insecticide widely used in agriculture in both developed and developing countries. However, this pesticide has a high toxicity not only to targeted insects but also to human and animals. In the present study, the enantiomers of methamidophos were enantiomerically separated by a semipreparative chiral liquid chromatography at the multimilligram scale on a polysaccharide-based chiral stationary phase and a preliminary evaluation of their in vitro inhibition of plasma butyrylcholinesterase (BChE) of hens was performed. In the present study, our first effort was to resolve the racemic mixture of methamidophos and to that end reversed-phase, normal-phase, and polar organic elution conditions were investigated in four different polysaccharide-based chiral phases. The best performance was achieved on a cellulose tris(3,5-dimethylphenylcarbamate) phase under normal phase. This chromatographic condition allowed the separation of 225?mg of methamidophos enantiomers with a high degree of chiral purity (>98%) in a short analysis time. Significant differences were found between the concentration that causes 50% of enzyme inhibition (IC50) of the three isoforms of methamidophos. (-)-Methamidophos showed an IC50 approximately three times larger than the (+)-enantiomer for plasma BChE of hens. Environ. Toxicol. Chem. 2012;31:239245. (C) 2011 SETAC
Keywords: Methamidophos; High-performance liquid chromatography; Chiral separation; Polysaccharide-based chiral phases; Butyrylcholinesterase